You should notice that if you multiply the bases of exponentials yields a difference of squares such that:

`(sqrt5-2)(sqrt5+2) = 5- 4 = 1`

Hence, `sqrt5+2 = 1/(sqrt5-2)`

You should come up with the substitution (sqrt5+2)^x = y such that:

`y + 1/y = 18`

You need to move the terms to the left side and you need to bring therms to a common denominator such that:

`y^2 - 18y + 1 = 0`

You should use quadratic formula to find `y_1` and `y_2` such that:

`y_(1,2) = (18+-sqrt(324 - 4))/2`

`y_(1,2) = (18+-sqrt(320))/2 =gt y_(1,2) = (18+-8sqrt(5))/2`

`y_(1,2) = 9 +- 4sqrt5`

You need to find x, hence you need to solve the equations `(sqrt5+2)^x = y_(1,2)`

Substituting `9 +- 4sqrt5` for `y_(1,2)` yields:

`(sqrt5+2)^x = 9 + 4sqrt5 =gt ln (sqrt5+2)^x = ln(9 + 4sqrt5)`

`x_1 = (ln(9 + 4sqrt5))/(ln (sqrt5+2))`

`x_2 =(ln(9- 4sqrt5))/(ln (sqrt5+2))`

**Hence, the solutions to exponential equation are `x_1 = (ln(9 + 4sqrt5))/(ln (sqrt5+2)) ` and `x_2 = (ln(9 - 4sqrt5))/(ln (sqrt5+2)).` **